Normal tissue outlining guidelines development for soft tissue sarcoma of the extremities - Rita Simões; Sarah Gulliford; Punita Shah; Eve McAtavey; Elizabeth Richardson; Umme Chowdhury; Laura Fray; Roeum Butt; Yolanda Augustin; Ruqayyah Sarang; Refia Kilinc; Maryam Iqbal; et al. (Clinical and Translational Radiation Oncology)
Introduction: Radiotherapy (RT) plans for soft tissue sarcoma of the extremities (STSE) are optimised to achieve maximum target coverage whilst avoiding high doses to weight-bearing bones and intermediate doses to the normal tissue (NT) limb corridor. Within this study, novel lower extremity NT outlining guidelines and atlas were developed based on the hypothesis that using these for RT planning may reduce RT toxicity. Usability and applicability of the guidance were also investigated. Methods: Guidelines for NT outlining were developed. Two STSE cases were selected and a set of reference volumes was outlined on each case by one Therapeutic Radiographer/Radiation Therapist (RTT) and peer-reviewed by a consultant radiation oncologist (RO). NTs were then outlined following the guidelines by 11 (8 RTT and 3 RO) and 12 (9 RTT and 3 RO) additional observers, respectively for cases 1 and 2. Dice coefficient (DICE), Maximum Hausdorff distance (maxHD) and mean surface distance (MSD) were calculated for individual NT volumes against the reference volumes. The Kruskal-Wallis test was performed. Analysis of interobserver variability was then used to inform guidance improvement. Results: Good agreement and reproducibility were observed in DICE, MSD and maxHD for the anterior, posterior, adductor and gluteal muscle compartments, femur and femoral head and neck, knee and hip joints. Moderate agreement was observed for the lateral rotator and iliopsoas muscle compartments, and the femoral and inguinofemoral neurovascular bundle. Poor agreement was observed for the deep thigh neurovascular bundle. Conclusion: Our results identify that the new NT outlining guidance for STSE is reproducible between observers and within a multi-professional environment, with consistent RTT and RO scores. This reproducibility is attributed to the use of guidelines. This study has also identified areas for refinement of the guidelines, particularly for the deep thigh neurovascular bundle.